(untitled) (Journal of Parents and Teachers, 2013)
Developing undertaking capacities and abilities is a way for reaching a more competitive society with a higher talent and more possibilities in a more and more globalized context. Under this budget, the Junta de Castilla y León has started a technique called “Educating for undertaking” that is present in all the educative levels.